Faktor-Faktor Yang Mempengaruhi Tax Avoidance Pada Perusahaan Pertambangan Yang Terdaftar Di BEI - Nova Choirul Anwar Pratama (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2020)
Governments and taxpayers have different interests, causing a tendency to tax avoidance. The purpose of this study to determine and analyze the impact of leverage, independent commissioner, firm size, institutional ownership, audit committee and audit quality to tax avoidance in mining companies listed in Indonesia Stock Exchange from 2013 - 2017. The study population was 43 mining companies listed in Indonesia Stock Exchange from 2013 - 2017 by using purposive sampling technique was chosen as 6 companies that meet the criteria of the sample. The method used is multiple linear regression analysis. The results showed independent commissioner effect on tax avoidance. While leverage, firm size, institutional ownership, audit committees and audit quality have no effect on tax avoidance. The benefits of this research are as a reference input for the company to assess and analyze the impact of leverage, independent commissioner, firm size, institutional ownership, audit committees and audit quality to tax avoidance. And can be used by investors as an input in the decision to invest in the company.